Primary Colors Red, Yellow, and Blue Use as Self-Cleaning Paints with Layer of Titanium Dioxide (Baghdad Science Journal, 2019)
Transparent nano- coating was prepared by Sol-Gel method from titanium dioxide TiO2 which has the ability to self-cleaning coating used for hospitals, laboratories, and places requiring permanent sterilization. Three primary colors are selected (red, blue, and yellow) as preliminary study to the effect of these colors on the nano-coating. Three traditional oil paints color were used as base, then coated by a layer of TiO2-Sol and deposited on the paints. The optical properties of TiO2-Sol were measured; the maximum absorption wavelength at (λmax=387 nm), the refractive index (n=1.4423) and the energy band gap (Eg=3.2 eV). The structure properties found by X-ray diffraction of TiO2-Sol illustrated that TiO2-Sol is polycrystalline nanoparticle have anatase phase also the morphological properties measured by Scanning Electron Microscopy (SEM) obetained the average grain size of TiO2-Sol was (50.427 nm). Self-cleaning properties measured by tensiometer dives. The best color gave the highest response to self-cleaning is the yellow color where the contact angle before exposure to UV ( = 101.47º ,at t = 0 min) and after exposure over time ( = 1.75º ,at t = 50 min), thus the water sheet of the surface and remove all contaminants.